People's Republic of China : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper examines the drivers and prospects for high levels of savings in China. China has one of the highest levels of national savings in the world, which is at the heart of its external and internal imbalances. High and rising household savings have mainly resulted from demographic changes as a result of the one-child policy and the breakdown of the social safety net during the transition from a planned to a market economy. Demographic changes will put downward pressure on national savings. Policy efforts to strengthen the social safety net and reduce income inequality are also needed to reduce savings further and faster and to boost consumption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet